2012
DOI: 10.4236/jbise.2012.59063
|View full text |Cite
|
Sign up to set email alerts
|

About the structure of posturography: Sampling duration, parametrization, focus of attention (part II)

Abstract: There exists a great variety of posturographic parameters which complicates the evaluation of center of pressure (COP) data. Hence, recommendations were given to use a set of complementary parameters to explain most of the variance. However, it is unknown whether a dual task paradigm leads to different parametrization sets. On account of this problem an exploratory factor analysis approach was conducted in a dual task experiment. 16 healthy subjects stood on a force plate performing a posture-cognition dual ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
(63 reference statements)
1
12
0
Order By: Relevance
“…In previous studies, the special influence of the measurement time on the frequency-dependent parameters has already been proven [7]. Several studies have already shown that 95% of the frequency components of the CoP's are below 1 Hz [7,17]. This finding coincides with the results of Durate and Zatsiorsky, among others.…”
Section: Digital Filterssupporting
confidence: 83%
See 2 more Smart Citations
“…In previous studies, the special influence of the measurement time on the frequency-dependent parameters has already been proven [7]. Several studies have already shown that 95% of the frequency components of the CoP's are below 1 Hz [7,17]. This finding coincides with the results of Durate and Zatsiorsky, among others.…”
Section: Digital Filterssupporting
confidence: 83%
“…It could be seen that a longer measurement time produces more reliable results and is therefore preferable. Based on the findings of this study, they recommended using a measurement period of at least 120 s. If the test setup allows, if possible, even a measurement period of 300 s should be chosen [17].…”
Section: Sampling Duration Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Movements of the CoP were calculated with Matlab 7.8 (MathWorks) following to the recommendations of Schubert et al [10]. For each participant, suit condition, and dependent variable, the mean value and the standard deviation of the mean were computed.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of posturography recording is not standardized. While short durations (typically 30 s) are commonly used in clinics, longer durations might allow more discriminative power on non-linear parameters ( Schubert et al, 2012a , b ). Our 51.2-s recording is thus a compromise between short recordings avoiding the occurrence of transient and particular events due to postural changes and consequently deteriorating measures related to sway area, and long recordings allowing a better accuracy in time-frequency analysis.…”
Section: Experiments 1: Posturographymentioning
confidence: 99%